Perioperative Complications in Obese Patients Undergoing Anterior Lumbar Interbody Fusion: Results From 938 Patients. (1st September 2019) - Safaee, Michael; Tenorio, Alexander; Amara, Dominic; Lai, Lillian; Molinaro, Annette; Hu, Serena; Tay, Bobby; Burch, Shane; Berven, Sigurd; Deviren, Vedat; Dhall, Sanjay S; Chou, Dean; et al.
Abstract: INTRODUCTION: Anterior lumbar interbody fusion (ALIF) is a versatile procedure with a role in the treatment of diverse lumbar pathologies. There are limited data on the effect of body mass index (BMI) and obesity on perioperative complications using this technique. METHODS: Patients undergoing ALIF from 2007 to 2016 at a single academic center were analyzed. Obesity was defined as BMI = 30. The primary outcome was any perioperative complication, classified as intraoperative or postoperative. Intraoperative complications included vascular injury, visceral/bowel injury, and medical/cardiac. Postoperative complications included neurologic deficit, hematoma, wound complications (dehiscence, hernia, infection), ileus, and medical complications including deep venous thrombosis, urinary tract infection (UTI), pneumonia, and others. Univariate and multivariate analyses were used to assess potential associations with obesity and perioperative complications. RESULTS: A total of 938 patients were included with mean age of 57 yr and 511 females (55%). Mean BMI was 28.7 with 354 (38%) of patients classified as obese. Complication rates were higher for obese vs nonobese patients (38.4% vs 30.5%, P  = .013), a difference that was driven primarily by postoperative complications (37.6% vs 27.7%, P  = .002) rather than intraoperative complications (3.4% vs 4.6%, P  = .359). Obese patients had significantly higher rates of ileus (12.1% vs 7.0%, P  = .008), wound-related complications (12.7% vs 4.8%, P  < .001), and UTI (5.1% vs 2.4%, P  = .028). In a multivariate model, age and obesity were associated with postoperative complications. CONCLUSION: Obesity is associated with increased perioperative complications in ALIF. Interestingly, the rate of intraoperative complications was similar to nonobese patients. The increased complication rate was driven primarily by immediate postoperative complications including ileus, wound complications, and UTI. Obese patients warrant careful preoperative medical optimization and close monitoring in the postoperative setting.